Empagliflozin prevents neointima formation by impairing smooth muscle cell proliferation and accelerating endothelial regeneration - Dutzmann, Jochen; Bode, Lena Marie; Kalies, Katrin; Korte, Laura; Knöpp, Kai; Kloss, Frederik Julius; Sirisko, Mirja; Pilowski, Claudia; Koch, Susanne; Schenk, Heiko; Daniel, Jan-Marcus; Bauersachs, Johann; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Empagliflozin, an inhibitor of the sodium glucose co-transporter 2 (SGLT2) and developed as an anti-diabetic agent exerts additional beneficial effects on heart failure outcomes. However, the effect of empagliflozin on vascular cell function and vascular remodeling processes remains largely elusive. Methods/Results: Immunocytochemistry and immunoblotting revealed SGLT2 to be expressed in human smooth muscle (SMC) and endothelial cells (EC) as well as in murine femoral arteries. In vitro, empagliflozin reduced serum-induced proliferation and migration of human diabetic and non-diabetic SMCs in a dose-dependent manner. In contrast, empagliflozin significantly increased the cell count and migration capacity of human diabetic ECs, but not of human non-diabetic ECs. In vivo, application of empagliflozin resulted in a reduced number of proliferating neointimal cells in response to femoral artery wire-injury in C57BL/6J mice and prevented neointima formation. Comparable effects were observed in a streptozocin-induced diabetic model of apolipoprotein E-/- mice. Conclusive to the in vitro-results, re-endothelialization was not significantly affected in C57BL/6 mice, but improved in diabetic mice after treatment with empagliflozin assessed by Evan’s Blue staining 3 days after electric denudation of the carotid artery. RNA sequencing of human SMCs identified the vasoactive peptide apelin to be decisively regulated in response to empagliflozin treatment. Recombinant apelin mimicked the in vitro-effects of empagliflozin in ECs and SMCs. Conclusion: Empagliflozin significantly reduces serum-induced proliferation and migration of SMCs in vitro and prevents neointima formation in vivo, while augmenting EC proliferation in vitro and re-endothelialization in vivo after vascular injury. These data document the functional impact of empagliflozin on vascular human SMCs and ECs and vascular remodeling in mice for the first time.